Gender Differences In Question Tags And Performative Utterances In Enola Holmes - Yohana Andrea Manalu; Findi Manik; Prima Jaya Daeli; Romaito Br Marbun; Vivi Novalia Sitinjak (Pustaka Digital Indonesia, 2026)
This study examines gender differences in the use of question tags and performative utterances in the film Enola Holmes (2020). Using Jennifer Coates’ theory of gender and language and speech act theory, the research examines how these linguistic features function in relation to power, politeness, and identity construction within a patriarchal Victorian context. A qualitative descriptive method was employed, with data taken from the film script and analyzed through pragmatic and textual approaches. The findings show that female characters, particularly Enola Holmes, use question tags more frequently and for diverse pragmatic functions, such as emotional confirmation, rhetorical questioning, and negotiation of meaning. These uses are not signs of uncertainty but serve as strategic interactional resources to assert agency and challenge male authority. Male characters tend to use more performative utterances in the form of commands, reflecting their institutional power. Overall, the study supports the view that gendered language differences are socially constructed.